Feeding behaviour of Caenorhabditis elegans is an indicator of Pseudomonas aeruginosa PAO1 virulence - Lewenza,Shawn; Charron-Mazenod,Laetitia; Giroux,Lauriane; Zamponi,Alexandra D (PeerJ PrePrints, 2014)
Caenorhabditis elegans is commonly used as an infection model for pathogenesis studies in Pseudomonas aeruginosa. While the standard virulence assays rely on the slow and fast killing or paralysis of nematodes, here we developed a behaviour assay to monitor the preferred bacterial food sources of C. elegans. The type III secretion system is a well-conserved virulence trait that is not required for slow or fast killing of C. elegans. However, ΔexsE mutants that are competent for hypersecretion of ExoS, ExoT and ExoY effectors were avoided as food sources in binary assays. Conversely, mutants lacking the secretion machinery or type III effectors were preferred food sources for PAO1. In binary feeding assays, both food sources were ingested and observed in the gastrointestinal tract, but non-preferred food sources were ultimately avoided. Next we developed a high throughput feeding behaviour assay to test a library of 2370 transposon mutants in order to identify preferred food sources. After primary and secondary screens, 37 mutants were identified as preferred food sources, which included mutations in many known virulence genes and that showed reduced virulence in the slow killing assay. We propose that C. elegans feeding behaviour can be used as a sensitive indicator of virulence for bacterial strains that have moderate worm killing activity.
Keywords: Caenorhabditis elegans; Pseudomonas aeruginosa; type III secretion; nematode feeding behaviour; high throughput virulence model; food preferences